GABA And Glutamate - New Developments In Neurotransmission Research - Janko Samardzic (IntechOpen, 2018)
This book collates the contributions of a selected number of neuroscientists that are interested in the molecular, preclinical, and clinical aspects of neurotransmission research. The seven chapters in this book address the latest research/review data related to GABA/glutamate system's organization and function, the structure of receptors, subtypes and their ligands, as well as the translational approach and clinical implications. The book offers readers a rich collection of data regarding current and future applications of GABA and glutamate neurotransmission, including promising research strategies and potential clinical benefits.
English
Keywords: Life Sciences; Neuroscience; Molecular Neuroscience